The functions of code-switching in EFL classrooms / Suthagar Narasuman, Ahmad Zahir Wali and Zahra Sadry - Narasuman, Suthagar; Wali, Ahmad Zahir; Sadry, Zahra (Penerbit UiTM, 2019)
Code-switching is a concept which has existed in bilingual and multilingual societies and it occurs quite frequently in English as a second or foreign language classes. Especially when the learners are all bilinguals or multilinguals and they have to switch back and forth between their mother tongue and a second or foreign language. This paper is driven by the three objectives. First, the study investigates the situations which trigger code-switching in EFL classes in Balkh and Kandahar Universities of Afghanistan. Secondly, it investigatesthe perception ofAfghan EFL lecturers in these universities towards code-switching. Third, to find out how the EFL lecturers use code-switching as an effective strategy while teaching English in their classes. In this study, the qualitative research approach was used to collect data from four Afghan English language lecturers of the two universities via the interview method. The results of this study indicate that these Afghan EFL lecturers have a positive perception regarding code-switching and they are using it in certain situations which facilitate theirteaching and students’learning of the content, howeverthey also hold negative perception towards switching while teaching. The findings also show that the lecturers use code-switching in different situations such as when dealing with cultural issues that tend to be difficult to explain only in the target language, explaining grammar and new vocabulary, giving clear instructions, and instructing English for Specific Purposes (ESP) classes.